Behaviour Management in the Classroom: Improving the Quality of Education through Systematic Optimization of the Learning Environment - Putri, Dinda Febrianti; Agus R, Abu Hasan; Qushwa, Febriyanti Ghayatul; Setiawan Putri, Diah Maghfiroh; Widiasari, Firdausa; Zahro, Fatimatus; Baharun, Hasan (UAS PRESS, 2024)
This research explores effective behavior management strategies for improving the quality of education in the classroom environment. The main focus of the study is to identify and analyze how integrating moral values such as honesty, responsibility, and empathy in behavior management can influence learning effectiveness. The research method used is a qualitative approach with data collection techniques through observation, in-depth interviews, and analysis of documentation related to behavior management practices in various classes. The results showed that implementing systematic behavior management strategies, such as providing positive feedback, consistently enforcing rules, and creating a supportive learning environment, significantly increased student engagement, reduced distractions, and improved academic outcomes. The implications of this research highlight the importance of training teachers to implement effective behavior management strategies and the need to develop a structured learning environment to support better teaching and learning processes. This research contributes to understanding how effective behavior management can influence educational quality and provides practical recommendations for implementation in various educational settings.